Bentuk Penyajian Tari Tradisional Tau Nuhu Pada Sanggar Bliran Sina Watublapi Kecamatan Hewokloang Kabupaten Sikka (Muara Nada: Jurnal Pendidikan Seni, 2026)
The Tau Nuhu dance, also known as the war dance, is a traditional dance representing the glory and bravery of the Krowe knights, an ethnic group in the Sikka region. It has been passed down from generation to generation as a cultural heritage and as a ritual medium for honoring ancestors and praying for safety in daily life. This study examines how the Tau Nuhu dance is performed at the Bliran Sina Watublapi Studio in Hewokloang Subdistrict, Sikka Regency. The study aims to analyze and describe the performance of the dance in its cultural setting. This research used a qualitative approach with an ethnographic method. Data were collected through observation, interviews, and documentation, then analyzed descriptively. The findings show that the Tau Nuhu dance is accompanied by fading gong music and bamboo percussion. These instruments are played rhythmically in patterns of slow and fast beats, requiring the dancers to respond with agility and precision. The uniqueness of the dance lies in its movements, the dynamic rhythm of the music, and the variation of bamboo percussion that enhances the performance. The dance consists of several sections: Awi Alu, Mage Mot, Gere Alu, Tua Reta Lo’u, and the closing section, Lori Lolo. Female dancers wear utang, labu, and kalar, while male dancers wear lipa and kalar. In conclusion, the Tau Nuhu dance has deep cultural significance for the Watublapi community as an ancestral heritage that continues to be preserved.
Keywords: Tau Nuhu dance; performance form; traditional dance; Bliran Sina Watublapi Studio; Sikka Regency